Are We Violating the Human Rights of the World’s Poor? [Spanish] (2012)
A human rights violation involves unfulfilled human rights and a specific active causal relation of human agents to such non-fulfillment. This causal relation may be interactional; but it may also be institutional, as when agents collaborate in designing and imposing institutional arrangements that foreseeably and avoidably cause human rights to be unfulfilled. Readily available evidence suggests that (a) basic social and economic human rights remain unfulfilled for around half the world’s population and (b) the design of supranational institutional arrangement plays a major role in explaining why the poorer half of humanity is suffering a rapid decline in its share (now below three percent) of global household income. A strong case can be made, then, that people like myself – well-to-do citizens of influential states – collaboratively violate the human rights of the global poor on a massive scale.